Ethical Values and Organizational Culture Structure as Constructive Internal Conflict Resolution Instruments - Khayru, Rafadi Khan; Hardyansah, Rommy; Rojak, Jeje Abdul (Journal of Social Science Studies, 2021)
This research aims to analyze how ethics and organizational culture are used in resolving internal conflicts and their impact on overall organizational management. The research is conducted through a literature study approach by referring to various theoretical and empirical sources from reliable publications. The results show that organizational ethics, in the form of moral values such as justice, honesty, and responsibility, are able to shape constructive individual behavior in dealing with differences. Meanwhile, organizational culture becomes a normative medium that unites individuals in symbolic structures and collective habits that uphold social harmony. When both are implemented consistently, the conflict resolution process in the organization can take place more healthily and oriented towards the transformation of relations. The impact is seen in increased trust between individuals, clarity of internal procedures, and strengthening of a justice and transparent organizational climate. In other words, ethics and culture not only function as elements of identity, but also as strategic managerial tools in creating organizational stability and sustainability. This research confirms the importance of organizational investment in building ethical awareness and strengthening culture as an integral part of healthy and competitive governance.